2018
DOI: 10.1080/10253890.2018.1435639
|View full text |Cite
|
Sign up to set email alerts
|

Long-term programing of psychopathology-like behaviors in male rats by peripubertal stress depends on individual’s glucocorticoid responsiveness to stress

Abstract: Experience of adversity early in life and dysregulation of hypothalamus-pituitary-adrenocortical (HPA) axis activity are risk factors often independently associated with the development of psychopathological disorders, including depression, PTSD and pathological aggression. Additional evidence suggests that in combination these factors may interact to shape the development and expression of psychopathology differentially, though little is known about underlying mechanisms. Here, we studied the long-term conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
7
18
0
Order By: Relevance
“…We additionally asked whether individual differences in glucocorticoid responsivity to stress during peripuberty might be associated with the development of an aggressive phenotype and found that corticosterone response to stress indeed differed between aggressive and nonaggressive PPS subgroups, in a manner that was associated with subsequent aggressiveness. Our data are in line with previous work highlighting a link between abnormal glucocorticoid levels and aggressive behaviour (Haller, 2014;Haller, Millar, van de Schraaf, de Kloet, & Kruk, 2000;Kruk, Haller, Meelis, & de Kloet, 2013) and our own work using the peripubertal stress model revealing a role for glucocorticoids during peripubertal stress on the long-term programming of aggressive behaviours (Papilloud et al, 2018;Veenit, Cordero, Tzanoulinou, & Sandi, 2013;Walker & Sandi, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We additionally asked whether individual differences in glucocorticoid responsivity to stress during peripuberty might be associated with the development of an aggressive phenotype and found that corticosterone response to stress indeed differed between aggressive and nonaggressive PPS subgroups, in a manner that was associated with subsequent aggressiveness. Our data are in line with previous work highlighting a link between abnormal glucocorticoid levels and aggressive behaviour (Haller, 2014;Haller, Millar, van de Schraaf, de Kloet, & Kruk, 2000;Kruk, Haller, Meelis, & de Kloet, 2013) and our own work using the peripubertal stress model revealing a role for glucocorticoids during peripubertal stress on the long-term programming of aggressive behaviours (Papilloud et al, 2018;Veenit, Cordero, Tzanoulinou, & Sandi, 2013;Walker & Sandi, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, repetitive stress has been found to have differential impact on brain structure in more vs. less stress responsive rat strains (Bourgin et al, 2015;Magalhaes, Barriere, et al, 2017;Magalhaes, Bourgin, et al, 2017). Nonaggressive PPS rats, that had greater corticosterone responses to peripubertal stress, displayed more anxiety-like and less social behaviour, in accordance with the phenotype of recently developed high-corticosterone rat lines (Walker & Sandi, 2018;Walker, Zanoletti, Guillot de Suduiraut, & Sandi, 2017). The brain regions studied here are particularly responsive to the programming effects of stress and are still maturing during the peripubertal period (Andersen & Teicher, 2008;Romeo, Kaplowitz, Ho, & Franco, 2013;Spear, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, we confirmed that the three lines display a stable divergence in CORT responsiveness to stressors from the juvenile period throughout aging and a behavioral phenotype comparable to the one reported in young-adults from the same lines (Walker et al, 2017; Walker and Sandi, 2018; Huzard et al, 2019). Our results show that, as compared to Inter line rats, rats from the High line were high CORT responders, and those from the Low line were low CORT responders to stressful challenges throughout life.…”
Section: Discussionsupporting
confidence: 81%
“…Conversely, in agreement with the findings that stress affects reversal learning (Graybeal et al, 2011) and that glucocorticoids modulate mechanisms involved in reversal (Bryce and Howland, 2015; Myers et al, 2014; Raio et al, 2017), our data suggest that the Low CORT responding line may exhibit altered neural activity in key brain regions involved in flexible behaviors. In fact, our former analyses of these rats indicate that the Low line exhibits lower basal activity in the ventral orbitofrontal cortex (OFC), prefrontal cortex (mPFC) and hippocampus as compared to the High line (Walker and Sandi, 2018). Impaired behavioral flexibility during reversal learning in the water maze has been reported for both mice with mPFC damage and aged rats with altered neural encoding in the OFC (Latif-Hernandez et al, 2016; Schoenbaum, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The special issue is rounded off by four research articles presenting highly relevant new data and perspectives. First, Sophie Walker and Carmen Sandi present findings highlighting the importance of how stress during relevant developmental time windowsin this case, adolescence and pubertyshape adult aggression and social behavior in concert with genetic predispositions for high or low HPA axis reactivity (Walker & Sandi, 2018). Along the same line, Brittany Smith, Jim Herman, and colleagues report that adolescent environmental enrichment prevents behavioral and physiological consequences of adolescent chronic stress exposure specifically in female rats, highlighting the importance of gender and studying sex-specific differences in stress (patho)physiology (Smith et al, 2017).…”
Section: Stress At Its Best: the 1st Munich Winter Conference On Stressmentioning
confidence: 99%